Pengembangan Dashboard Sistem Persebaran Cyberbullying Pada Media Sosial Twitter - Aditya Wisnu Jati Kusumo; Fajar Pradana; Bayu Priyambadha (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Research in the field of communications technology today has grown rapidly. This is indicated by the use of the Internet as a medium of communication. The development of technology can cause harmful effects, such as cyberbullying. Cyberbullying is any form of violence committed in the virtual world that can cause health problems for victims, such as physical and psychological problems. Lack of concern about cyberbullying issues, and the unavailability of cyberbullying data to actuate preventive action is the problems to overcome cyberbullying issues. The study was conducted with the aim of seizing the attention of the government through the communications and informatics ministries on cyberbullying cases and can serve as a basis in mobilizing preventive actions, by providing data on cyberbullying and visualizing the information into a system dashboard. Stages in this study started from literature studies, information gathering, requirement analysis, design, implementation, and testing. In this research, there are several software development processes, which is done with waterfall development model. The developed system in this study is a web-based system that can display the percentage of cyberbullying in a location with data obtained from tweets on Twitter that have been classified using sentiment analysis. The developed system in this research integrates between the framework used, the Twitter API library as a data collector, and the library of sentiment analysis to classify the data. The testing strategy in this research is done by unit testing, integration testing, and validation testing, with the result all valid value for all test cases which means that the built system can run as intended and free from failure